Academic Supervision Management to Improve the Quality of Mathematics Learning in Madrasah Aliyah - Raudlatul Munawarah; Dadang Suherman; Waska Warta; R. Supyan Sauri (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
Academic supervision is the duties and responsibilities of academic supervisors, which the Principal/Madrasah can also carry out. This supervision activity can be delegated to more senior teachers who are concerned as coaches, so they are supervisors in carrying out their duties. However, the person concerned must still report the results of academic supervision activities to the principal/madrasah. The quality of learning can be said to be a picture of the good and bad results achieved by students in the learning process. Schools are considered quality if they change students' attitudes, behaviour, and skills about their educational goals. This study uses a qualitative method. In essence, there are many variations of management functions, Planning, Organizing and Staffing, Leading, Controlling. To support the realization of excellent madrasas, several roles of excellent teachers must be carried out. There are three duties as a profession, namely educating, teaching, and training. It is not enough to cram subject matter to students as a teacher.